Perbandingan Nitaqat dan Tawteen - Safira Novia Safitry; Agus Haryanto (Jurnal ICMES, 2019)
This article discusses how two Arab Gulf countries, namely Saudi Arabia and the United Arab Emirates (UAE), implemented policies for foreign workers. Saudi Arabia and the UAE have the same regulations to limit foreign workers namely Nitaqat for Saudi Arabia and Tawteen for the United Arab Emirates. The purpose of this article is to explain the difference between the two policies which have become national-scale state policies. In analyzing it, the writer uses political comparison theory. The results of this study indicate that Saudi Arabia and the UAE have the same reason why they implement policies to restrict foreign workers. The limitation of foreign workers is a regional phenomenon of the Gulf Cooperation Council (GCC) countries because these countries have started a sustainable development and paid attention to the importance of the labor sector which is reserved for citizens. In addition, the two countries have different experiences in the process of proposing policies related to the interests of the government and the industrial sector.